Faktor Yang Mempengaruhi Struktur Modal Perusahaan Industri Mesin dan Tenaga Kerja di Sumatera Utara yang Terdaftar pada Bursa Efek Indonesia - Putri Novyenni Widyarosa Tarigan; Ihsan Effendi; Wan Rizca Amelia (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
This research was conducted to determine the factors that affect the capital structure of manufacturing companies listed on the Indonesia Stock Exchange.The type of data in this study is secondary data. The data sources used are the financial statements of manufacturing companies listed on the Indonesia Stock Exchange and the company's annual financial statements obtained from the Indonesian Capital Market Directory.Sampling techniques used in this research are purposive sampling methods in basic industrial and chemical manufacturing companies, chemical sub-sectors listed on the Indonesia Stock Exchange research period 2009 – 2018.The data analysis technique used is factor analysis with SPSS program version 25.The result of analysis of capital structure factor is Ln total assets, Earning Before Interest and Taxes (EBIT), Net sales, Return On Equity (ROE) and Return On Asset (ROA) meet the requirements and able to explain each of the factors of the capital structure in the company.